THE IMPACT OF LANGUAGE MASTERY ON CRAFTING NEWS STORIES AND HEADLINES IN JOURNALISM - Fitriani, Yustina; Destianingsih, Arita; Satria, Ari (INOVISH JOURNAL, 2023)
This study delves into the correlation between language mastery and the proficiency in creating news stories and headlines within the field of journalism. It examines how language proficiency influences the effectiveness, clarity, and engagement of journalistic content. Through an analysis of language techniques, writing styles, and their impact on audience reception, this study seeks to uncover the intrinsic relationship between language mastery and the quality of news reporting. The findings underscore how students linguistic proficiency influences the depth, resonance, and impact of news narratives and headlinesKeywords: language mastery, Â news stories, headline.